Dynamic Performance Improvement of an Isolated Wind Turbine Induction Generator - Rahim, A.H.M.A. (2020)
A dynamic model of a variable speed stand alone wind generation unit is developed. The steady state as well as the dynamic performance of the wind system is explored. The necessary conditions for steady operation have been established. The performance of the system under variable wind gust and other disturbance conditions has been studied. It has been observed that a stand alone generator is very vulnerable to transient variations in the system. This is because of the lack of excitation to the unit. A stabilizing control scheme through a thyristor controlled variable capacitance at the generator terminal is suggested for stabilizing the system. PI controller with optimized gain settings is included in the control loop. The PI controlled variable capacitance strategy has demonstrated very good steady state and transient performance of the wind turbine-generator sy